2020
DOI: 10.3390/cancers12040922
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Biomarkers for the Prediction of Distant Metastasis in Head and Neck Squamous Cell Carcinoma

Abstract: Distant metastases (DM) in head and neck squamous cell carcinoma (HNSCC) remain a challenge as treatment options are limited. To identify biomarkers predictive of DM in primary tumors (PT), gene expression profiling was performed in PT from patients who did, or did not develop DM (T-with and T-without, n = 25 and 24, respectively), and in matched DM. A total of 185 and 42 differentially expressed genes were identified in the T-with vs. T-without and the T-with vs. DM comparisons, respectively. The intersection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
0
14
0
1
Order By: Relevance
“…from 79 HNSCC patients ( Peng et al, 2011 ), consisting of 37 HNSCC patients ( Estilo et al, 2009 ), from 270 HNSCC patients ( Wichmann et al, 2015 ), from 49 HNSCC patients ( Alfieri et al, 2020 ), and The Cancer Genome Atlas (TCGA) -HNSC cohorts including 546 HNSCC HTSeq-counts, methylation profiles and related clinical information were downloaded. CalcNormFactors was used to calculate normalization factors to scale the gene expression in TCGA dataset ( Anders & Huber, 2010 ; Le et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…from 79 HNSCC patients ( Peng et al, 2011 ), consisting of 37 HNSCC patients ( Estilo et al, 2009 ), from 270 HNSCC patients ( Wichmann et al, 2015 ), from 49 HNSCC patients ( Alfieri et al, 2020 ), and The Cancer Genome Atlas (TCGA) -HNSC cohorts including 546 HNSCC HTSeq-counts, methylation profiles and related clinical information were downloaded. CalcNormFactors was used to calculate normalization factors to scale the gene expression in TCGA dataset ( Anders & Huber, 2010 ; Le et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The most important prognostic determinant of HNSCC tumours is considered the presence of lymph node metastases, since lymphatic metastatic spread correlates with a significant decrease in the survival rate of patients [63]. TDE and communication with the TME are critical factors in tumour metastasis [64]. Theodoraki et al demonstrated that CD44v3 protein-carrying TDE are correlated with higher disease stages and lymph node metastasis; thus, TDE could potentially serve as a noninvasive biomarker of cancer progression [65].…”
Section: Tde Promote Metastasismentioning
confidence: 99%
“…Squamous cell carcinomas (SCCs) arise from stratified epithelia, and the most relevant organ sites are the skin and oral cavity where high UV irradiation, tobacco carcinogens, or human papillomavirus (HPV) infection are initiating events. The worst outcome of SCC is death caused by distant metastasis, most commonly to the lung ( Bohnenberger et al, 2018 ; Alfieri et al, 2020 ). Lung metastasis is the process of cancer cells disseminating from a primary SCC, entering into blood vessels or lymphatic vessels (intravasation), survival and traveling, and moving out of vessels (extravasation) into the lung, and survival and expansion in the lung thereafter ( Chaffer and Weinberg, 2011 ).…”
Section: Introductionmentioning
confidence: 99%